2018
DOI: 10.1371/journal.pone.0191489
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and survival of human amniotic epithelial cells during their hepatic differentiation

Abstract: Stem cells derived from placental tissues are an attractive source of cells for regenerative medicine. Amniotic epithelial cells isolated from human amnion (hAECs) have desirable and competitive characteristics that make them stand out between other stem cells. They have the ability to differentiate toward all three germ layers, they are not tumorigenic and they have immunosuppressive properties. Although liver transplantation is the best way to treat acute and chronic hepatic failure patients, there are sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 102 publications
(115 reference statements)
2
49
1
2
Order By: Relevance
“…AECs are unique because of their pluripotent status as stem cells, 45 as well as their co-expression and localization of epithelial and mesenchymal markers. The ability of cells to express both epithelial and mesenchymal phenotypes was first reported by Savagner as a metastable phenotype, documented in his studies of Rac distribution in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…AECs are unique because of their pluripotent status as stem cells, 45 as well as their co-expression and localization of epithelial and mesenchymal markers. The ability of cells to express both epithelial and mesenchymal phenotypes was first reported by Savagner as a metastable phenotype, documented in his studies of Rac distribution in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that hAEC can differentiate into hepatocyte-like cells under certain conditions (18,25,44). hAEC express significant levels of SOX-2, OCT-4, and NANOG and these genes diminish at the end of hepatic differentiation procedures and the cells begin to express mature hepatic genes.…”
Section: Hepatic Differentiation Of Haecmentioning
confidence: 94%
“…Moreover, hAESCs can be readily obtained and isolated from the placenta and are non-tumorigenic upon transplantation. They are almost entirely free from ethical and legal considerations [10,14,16]. In previous studies, hAESCs have been differentiated into neurons, glial cells, cardiomyocytes, and hepatocytes [8,10,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…They are almost entirely free from ethical and legal considerations [10,14,16]. In previous studies, hAESCs have been differentiated into neurons, glial cells, cardiomyocytes, and hepatocytes [8,10,[16][17][18][19][20]. In particular, recent studies have suggested that hAESCs are a promising candidate for the treatment of neurological diseases [18,21].…”
Section: Introductionmentioning
confidence: 99%